Lumped damage mechanics as a diagnosis tool of reinforced concrete structures in service: case studies of a former bridge arch and a balcony slab (Fracture and Structural Integrity, 2021)
Reinforced concrete structures may need repair in order to ensure the designed durability. Such necessity vary in cause and effect, but the structural diagnosis serves as the basis for adopting intervention measures. The assessment of the structural condition usually is made in loco, but sometimes numerical analyses are required as a low cost and effective preliminary diagnosis. In general, numerical analyses use hundreds or thousands of finite elements and nonlinear theories that are not often used in engineering practice. As an alternative, lumped damage mechanics (LDM) uses key concepts of classic fracture and damage mechanics in plastic hinges throughout well-known quantities such as ultimate moment and cracking moment. Such theory describes the concrete cracking by a damage variable, which can be used as a diagnosis criterion. Therefore, this paper presents LDM as a diagnosis tool to analyse actual structures. The case studies presented in this paper are a former bridge arch tested in China and a balcony that collapsed in Brazil. The results show that LDM numerical response of those structures are quite close to laboratory observations (former bridge arch) and in loco measurements (balcony).
Keywords: Lumped damage mechanics; Reinforced concrete; Diagnosis; Bridge arch; Balcony